Paving the Way for Future Medical Dermatology Leaders in Psoriasis and Psoriatic Arthritis: 1st Annual Mentoring Program for Dermatology Fellows. Issue 3 (September 2013) - Husni, M. Elaine; Duch, Daniel; Korman, Neil
There is a growing shortage of dermatologists in the United States, with fewer dermatologists concentrating on the management of chronic diseases such as psoriasis and psoriatic arthritis. There are no programs focused on fellows interested in medical dermatology. To address this need, a mentoring conference was developed for dermatology fellows. They were nominated for the program by their advisors, and selected based on their academic potential, research interests, and experience. The conference was highly interactive with a focus on building relationships with like-minded individuals interested in academic medicine. Faculty presented the most recent, clinically relevant knowledge regarding classification, diagnosis, and treatment of psoriatic diseases. Other topics included developing research questionnaires, solidifying a hypothesis, and optimizing interactions with a mentor. Fellows presented original research and were given the opportunity to respond to critiques. The conference was considered by all to be highly successful. Plans to strengthen and expand the program for next year are under way.